1990
DOI: 10.1007/bf00210074
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of genetic diversity among cytoplasms of Triticum and Aegilops

Abstract: Many related species and strains of common wheat were compared by matching differences among their mitochondrial genomes with their "parent" nuclear genomes. We examined three species of Aegilops, section Sitopsis (Ae. bicornis, Ae. sharonensis, and Ae. speltoides), emmer wheat (Triticum dicoccoides, T. dicoccum, and T. durum), common wheat (T. spelta, T. aestivum, and T. compaction), and timopheevi wheat (T. araraticum, T. timopheevi, and T. zhukovskyi). A single source of the cytoplasm was used in all the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…The proportion of variable bands differed from region to region and was the highest in the 3Ј flanking region of rbcL, in which 18 of 22 bands (81.8%) detected were variable. The high level of variation in this region was consistent with the high variation among nucleotide sequences in the same region (7,10). On the other hand, no variation was detected in the psbB region.…”
Section: Variations Detected By Sscp Analyses Of Ct and Mtdnassupporting
confidence: 80%
See 1 more Smart Citation
“…The proportion of variable bands differed from region to region and was the highest in the 3Ј flanking region of rbcL, in which 18 of 22 bands (81.8%) detected were variable. The high level of variation in this region was consistent with the high variation among nucleotide sequences in the same region (7,10). On the other hand, no variation was detected in the psbB region.…”
Section: Variations Detected By Sscp Analyses Of Ct and Mtdnassupporting
confidence: 80%
“…Even though sequencing analyses are not as thorough as the RFLP analyses, the sequence of one chloroplast gene (rbcL, for the Rubisco large subunit) from seven Triticum and Aegilops species indicated that Ae. speltoides is the donor of both the plasmon and B genome of common wheat (7).…”
mentioning
confidence: 99%
“…These characters have been extensively used in studying phylogenetic relationships (Chowdhury and Smith, 1988;Wang et al, 2000;Yang et al, 1998), exploring plant geographic distribution (Tozuka et al, 1998), and evaluating mtDNA variation and diversity (Muza et al, 1995;Terachi et al, 1990). It is distinguished from nuclear DNA by many unique characteristics, including a relatively higher mutation rate, simple structure, fast evolution, and genetic independence.…”
Section: Genetic Diversity and Classification Of Cytoplasm Of Chinesementioning
confidence: 99%
“…speltoides Tausch was the most likely diploid species for the donor of BB and GG genomes. This idea was supported by RFLP analyses of chloroplast DNA (Ogiwara and Tsunewaki 1988;Miyashita et al 1994;Wang et al 1997;Yamane and Kawahara 2005), mitochondrial DNA (Terachi et al 1990) and nuclear polymorphic DNA (Dvorak and Zhang 1990;Mori et al 1995;Sasanuma et al 1996;Huang et al 2002). Previous studies suggested that T. timopheevii ssp.…”
Section: Introductionmentioning
confidence: 85%